Respostas

2014-05-06T21:03:44-03:00
x² - 5x + 6 = 0
a = 1
b = -5
c = 6
       Δ = b² - 4ac
       Δ = (-5)² - 4 . 1 . 6
       Δ = 25 - 24
       Δ = 1
                x =  - b ± √Δ 
                           2a
                x =  - (-5) ± √1 
                           2 . 1
                x' =  5 - 1  = 2         
                          2        2
                x'' =  5 + 1  =  6  = 3               
                          2         2 

RESP.: 2 e 3 (alternativa B)

Espero ter ajudado. Valeu!